Allelopathic Effects of Aqueous Extracts From Sesame Leaves and Root on the Germination and Seedlings Growth of Maize and Sorghum - Abdulaziz, Bilkisu; Nayaya, A.J.; Yakubu, M.N. (International Journal of Scientific Research in Biological Sciences, 2024)
A laboratory and screen house experiment was carried out to investigate the allelopathic impacts of sesame (Sesamum indicum) leaf and root extracts at concentrations of 0%, 5%, 25%, 50%, and 75% on the germination, root and shoot development, seedling growth, plant height, leaf count, fresh and dry weight, germination rate, germination percentage, and photosynthetically active radiation in maize and sorghum seedlings. The findings revealed that the highest germination rates occurred at 5% and 25% concentrations, as well as in the control plants, showing statistically significant differences at (P<0.05). Conversely, germination was reduced at 50% concentration and completely inhibited at 75% concentration in root extract treatments. Measurements of plumule and radicle length, along with fresh and dry weights, demonstrated notable differences in maize when compared to sorghum. Moreover, root growth exhibited greater sensitivity to the allelopathic effects than shoot growth, a pattern similarly reflected in plant height and leaf numbers. The vigor index, germination rate index, and germination percentage were highest in the 5%, 25%, and control treatments for both maize and sorghum, while these parameters were lowest at 50% and 75% concentrations. These results indicate that lower concentrations of leaf or root extracts exert minimal effects on germination and seedling development in both maize and sorghum, with the intensity of the impact being concentration-dependent.